Nicotine-induced mitophagy in bronchial epithelial cells and MYST1 downregulation in cigarette smoke–exposed lungs: potential mechanisms of COPD progression - Kai Liu; Dongchuan Xu; Jie Zhao; Rubing Mo; Mei Lin; Chanyi He; Qi Lin; Tian Xie; Quanni Li; Yipeng Ding (Molecular Biology Reports, 2026)

Mechanistic insights into the migration and transformation of As2O3 by HCl during simulated MSW incineration flue gas cooling - Shuai Li; Hongyun Hu; Peixiong Tan; Chan Zou; Yongda Huang; Yipeng Wang; Zhong Lin; Hong Yao (Fuel, 2026)

Sustainable photothermal superhydrophobic coatings based on magnetically recyclable MOF-derived carbon for efficient anti/de-icing - Jiaxing Zhang; Peijian Sun; Weijie Lin; Yipeng Wang; Xin Cui; Mengyue Wang; Xuehui Sun; Peipei Zhang; Bin Yan (Chemical Engineering Journal, 2026)

Effects of O-ring defects on sealing performance of a pressure-testing valve assembly for seabed coring - Shengyuan Huang; Jialiang Wang; Bo Li; Yongzheng Jiang; Haitao Zheng; Yipeng Ma; Zhiyuan Zhang; Lian Lin (Marine Georesources & Geotechnology, 2026)

Cenozoic uplift and paleoclimate history of the Southeastern Tibetan Plateau - Ya Cui; Lin Li; Yang Wang; Yuyang Wang; Yipeng Zhang; Bo Zhang; Jinjiang Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Environmental controls and nonlinear responses of the diatom-dinoflagellate ratio in Jiaozhou Bay - Yipeng Huang; Zhengguo Cui; Changhua Liu; Dongsheng Ding; Lin Zhu; Keming Qu; Yuqiu Wei; Jun Sun (Marine Pollution Bulletin, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Iron-modified cement hydration regulates DOM transformation and carbon stabilization in soil-concrete systems during rainfall-runoff - Qiao Li; Yipeng Wang; Jiuxian Yang; Wenyou Wu; Jiyuan Jin; Xinchao Zhang; Yuanyuan Pei; Lin Gu (Environmental Research, 2026)

Control of crustal strength by crustal melt presence and removal and its influence on the deformation mode in the Himalayan orogen - Yipeng Li; Delores M. Robinson; Lin Ding; Kathryn Metcalf (Earth and Planetary Science Letters, 2025)

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Recent advances in 3D cell culture models in cancer drug development - Yae Sol Cha; Alvin Michaels; Janney Z. Wang; Yihe Niu; Yipeng Lin; Ling Zhu; Xue Zhu; Ke Wang; Michael Murray; Fanfan Zhou (Journal of Pharmaceutical Investigation, 2025)
Background In vitro cell culture models are widely used in cancer drug development. However, traditional two-dimensional (2D) models do not replicate the complex characteristics of the tumour microenvironment. Three-dimensional (3D) culture models have been used to prepare cell spheroids that are increasingly used in drug screening and evaluation due to their greater capacity to mimic tumour properties. Area covered This review discusses the methods used to generate 3D cell systems and their applications in cancer research. There are several methods used in the generation of 3D culture models, including forced floating and matrix-based methods. However, bioprinting technologies have emerged more recently as novel approaches to generate 3D culture models that can better mimic tumour physiology. 3D models are used to evaluate the activities of drugs in a wide variety of cancer types, although they have not yet been widely applied in the case of rarer cancers. Expert opinion 3D culture models have a number of desirable features that are advantageous in anti-cancer drug development. However, some methods of spheroid production have issues of inherent non-reproducibility and inconsistency, while bioprinting technology generally has more favourable features. Thus, newer optimised technologies will improve the physiochemical properties of spheroids, which may promote their application in cancer drug development.

Experimental study on the effect of different sealing ratios on the behavior of continuous spill fires in sloped tunnels - Weibing Jiao; Changkun Chen; Wuhao Du; Zida Lin; Yipeng Bao; Shishan Liu (Tunnelling and Underground Space Technology, 2025)

An empirical genesis index of Tibetan Plateau vortex and its relationship with environmental factors - Zhiqiang Lin; Weidong Guo; Yipeng Cao; Xiuping Yao; Jun Du; Zhenbo Zhou; Dongsheng Su (Climate Dynamics, 2025)

Si-based all-lithium-reactive high-entropy alloy for thin-film lithium-ion battery anode - Yi Su; Xincheng Lei; Wenjie Chen; Yipeng Su; Haowen Liu; Shuaiyang Ren; Ruoyu Tong; Yitao Lin; Weijing Jiang; Xiaozhi Liu; Dong Su; Yuegang Zhang (Chemical Engineering Journal, 2024)

Experimental study on the burning characteristics and smoke temperature distribution of continuous spill fires in sloped tunnels - Weibing Jiao; Changkun Chen; Zida Lin; Yipeng Bao; Lang Shi (Tunnelling and Underground Space Technology, 2024)

UV aging may enhance adsorption capacity of Poly (butylene adipate-co-terephthalate) (PBAT) to heavy metals and toxicity to zebrafish - Xing Cheng; Yipeng Hou; Xubing Lin; Chudan Wang; Baozhen Shen; Shengchi Zhuo; Zhen Li; Licheng Peng; Zengjian Su (Aquatic Toxicology, 2024)

Effects of ultrasonic pretreatment on fibrillation kinetics, morphologies, and functional properties of bovine serum albumin fibrils - Yipeng Yang; Ziran Pan; Tangyu Yang; Huaijie Yang; Lin Li; Bing Li (Food Hydrocolloids, 2024)

Ultrasonic treatment treated sea bass myofibrillar proteins in low-salt solution: Emphasizing the changes on conformation structure, oxidation sites, and emulsifying properties - Meijuan Lan; Tongshuai Li; Lin Li; Shaoyun Wang; Juncheng Chen; Tangyu Yang; Zhiru Li; Yipeng Yang; Xia Zhang; Bing Li (Food Chemistry, 2024)

Phenolic composition and antioxidant capacity of betel inflorescence extract in a simulated oral environment - Pangzhen Zhang; Ahmad Reza; Emily Ng; Kimtrang Nguyen; Sheng Lin; Zijian Liang; Yipeng Chen; Nicola Cirillo (Food Chemistry, 2024)

Diagenetic differentiation of tuffaceous interstitial materials in sandy conglomerate and their effect on reservoir properties - Peng Qin; Denglin Han; Binyu Ma; Xingyao Zeng; Yipeng Lin (Marine and Petroleum Geology, 2023)

Reexamination of traditional testing techniques for determining WRCs of woven geotextiles in full suction range - Chuang Lin; Yipeng Guo; Xiong Zhang; Javad Galinmoghadam (Geotextiles and Geomembranes, 2023)

Microbial response to antimony-arsenic distribution and geochemical factors at arable soil around an antimony mining site - Huayan Huang; Kangkai Lin; Ling Lei; Yongyun Li; Yipeng Li; Ke Liang; Yuxian Shangguan; Heng Xu (Environmental Science and Pollution Research, 2023)

Deep learning based diagnosis of Parkinson’s Disease using diffusion magnetic resonance imaging - Hengling Zhao; Chih-Chien Tsai; Mingyi Zhou; Yipeng Liu; Yao-Liang Chen; Fan Huang; Yu-Chun Lin; Jiun-Jie Wang (Brain Imaging and Behavior, 2022)

Preliminary study of genome-wide association identified novel susceptibility genes for thyroid-related hormones in Chinese population - Liang Huang; Fenghua Bai; Yutian Zhang; Shanshan Zhang; Tianbo Jin; Xingwei Wei; Xiaoli Zhou; Mei Lin; Yufei Xie; Chanyi He; Qi Lin; Tian Xie; et al. (Genes & Genomics, 2022)

Preliminary study of genome-wide association identifies novel susceptibility genes for serum mineral elements in the Chinese Han population - Duojian Guo; Yu Zhou; Xingwei Wei; Shanshan Zhang; Tianbo Jin; Yutian Zhang; Mei Lin; Xiaoli Zhou; Yufei Xie; Chanyi He; Qi Lin; Ping He; et al. (Biological Trace Element Research, 2022)

An experimental study of the impacts of solar radiation and temperature on mercury emission from different natural soils across China - Han Xie; Maodian Liu; Yipeng He; Huiming Lin; Chenghao Yu; Chunyan Deng; Xuejun Wang (Environmental Monitoring and Assessment, 2019)